2022
DOI: 10.1002/etc.5339
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Atrazine on Chlorophyceae Species and Association with Morphology, Photosynthesis, Chlorophyll Content, and Glutathione‐S‐Transferase Activity

Abstract: Atrazine is a herbicide widely used in the control of weeds in crops such as corn, sugar cane, and sorghum. It is often found in aquatic environments, where it can potentially endanger nontarget organisms such as microalgae. The present study evaluated atrazine toxicity to seven different species of Chlorophyceae and the tolerance of the species to the herbicide was related to morphological, photosynthetic, chlorophyll‐a content and the activity of the glutathione‐S‐transferase enzyme (GST). The comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…On the other hand, although the effect of archaea on the activity of the detoxifying enzyme GST is understudied, Selim et al demonstrated that species of the archaea genus Haloferax were able to promote the enzymatic activity of the detoxifying enzyme GST [59]. Furthermore, the ability of diverse microalgae to promote GST enzyme activity has been previously described by some authors [60][61][62].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, although the effect of archaea on the activity of the detoxifying enzyme GST is understudied, Selim et al demonstrated that species of the archaea genus Haloferax were able to promote the enzymatic activity of the detoxifying enzyme GST [59]. Furthermore, the ability of diverse microalgae to promote GST enzyme activity has been previously described by some authors [60][61][62].…”
Section: Discussionmentioning
confidence: 97%